‘UNEDUCATED’, ‘IGNORANT’, OR EVEN ‘ILLITERATE’? ASPECTS AND BACKGROUND FOR AN UNDERSTANDING OF AΓPAMMATOI (AND IΔIΩTAI) IN ACTS 4.13 - Kraus, Thomas J. (New Testament studies, 1999)
In Acts 4.13 Peter and John are designated as αγραμματoι... και ιδιωται. Is that phrase meant as a harsh disparagement of the two apostles by the members of the Sanhedrin? On the basis of lexical, contextual, and social-historical evidence this study argues against an evaluation of the double qualification through the eyes of modern people with their usual disregard for illiterates (and non-specialists). The documentary papyri especially present a different, unbiased picture without any social or negative impact of illiteracy and non-specialism. They help to clarify Acts 4.13 and make the terms ‘illiterate people’ and ‘laymen’ acceptable.